1996
DOI: 10.1159/000188941
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Calcium Signalling and Vascular Reactivity in Bartter’s Syndrome

Abstract: We investigated patients affected by Bartter’s syndrome in the attempt to localize the intracellular defect mediating the reduced intracellular Ca2+ mobilization that may be responsible for the decreased vascular reactivity characteristic of Bartter’s syndrome. Using the formylmethionyl-leucyl-phenylalanine (fMLP) receptor system, which causes intracellular calcium release, we investigated fMLP-stimulated intracellular inositol 1,4,5-trisphosphate (IP3) production as well as the number and affinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…We showed, in fact, in Bartter's and Gitelman's patients [15] an anomaly in the intracellular Ca 2+ and IP 3 signaling system [16,17], a reduced protein kinase C activity [17,18] and upregulation of the nitric oxide system [19,20]. We have also studied aspects of these diseases connected with electrolyte abnormalities [21] and, more recently, with magnesium handling and chondrocalcinosis [22].…”
mentioning
confidence: 99%
“…We showed, in fact, in Bartter's and Gitelman's patients [15] an anomaly in the intracellular Ca 2+ and IP 3 signaling system [16,17], a reduced protein kinase C activity [17,18] and upregulation of the nitric oxide system [19,20]. We have also studied aspects of these diseases connected with electrolyte abnormalities [21] and, more recently, with magnesium handling and chondrocalcinosis [22].…”
mentioning
confidence: 99%
“…Furthermore, although in this study no calcium measure ments have been presented, in all the patients included in this study we previously reported not only a reduced intracellular calcium release [5], but we also recently showed a reduced inositol 1,4,5-triphosphate (IP3) pro duction [6] that, along the calcium-dependent signal transduction sequence, causes calcium release and pro tein kinase C activation [14], Therefore, the reduced intracellular IP3 production and calcium release found in our patients together with the results of the present study, strongly point toward a relationship, in Bartter's syn drome, between the defective myocardial contractile re cruitment and the altered intracellular calcium handling.…”
Section: Discussionmentioning
confidence: 85%
“…In fact, in addi- tion to defects in vascular smooth muscle calcium-dependent processes (reduced the response to AT II and norepi nephrine) [ 1 ], a number of defects in physiologic activities related to decreased response to Ca2+ mobilizing stimuli (anomalies in shape changes and aggregation) have been demonstrated also in platelets of patients affected by Ban ter's syndrome [4]. Furthermore, we have reported that patients affected by Bartter's syndrome exhibit a smaller than normal increment of neutrophil intracellular Ca2+ release [5] and we have recently shown where in the intra cellular signal transduction system the basic anomaly responsible for the decreased mobilization of intracellular Ca2+ is located [6], This anomaly in intracellular calcium handling could cause the hyporesponsiveness of Bartter's syndrome's vascular smooth muscle [6] as it is well known that the contractile response of vascular smooth muscle is strongly dependent on cytosolic Ca2+ levels [7], This anomalous intracellular calcium homeostasis could also be due an anomaly of myocardial contractile reserve recruitment since inotropic activation depends on the ability to adequately increase intracellular calcium [8].…”
Section: Introductionmentioning
confidence: 96%
“…Recently, however, down-regulation in response to the chronic high levels of renin and aldosterone has been considered to be the cause [7][8][9][10]. In Bartter's syndrome, the increase in intracellular calcium ions is suppressed at the second messenger level, and therefore vascular and myocardial reactivity is decreased [11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%